(untitled) (International Journal of Innovative Technologies in Economy, 2019)
The development of trade between China and Mongolia should be based on complementary product trade. On this basis, products with trade potential should be continuously explored to expand the scale and structure of China- Mongolian trade and promote the continuous development of bilateral trade. This paper analyzes the current situation of economic and trade cooperation and trade complementarity between China and Mongolia, and concludes that China and Mongolia have different comparative advantages in export products. Mongolia’s export is highly integrated with China’s trade, and the two countries are highly complementary in trade.